Implikasi Penolakan Penerbitan Surat Keterangan Ghaib Terhadap Hak Pencari Keadilan di Pengadilan Agama Purwokerto - Adi, Luthfi Kalbu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2025)
A husband or wife who has been abandoned by their spouse without knowing their whereabouts has the right to file a lawsuit or request permission for a divorce decree to the Religious Court according to their domicile or place of residence. Filing for divorce through this scheme requires an administrative requirement in the form of a letter of absence issued by the village/sub-district office where the defendant last resided. However, not all village or sub-district offices have standard operating procedures (SOPs) for issuing these certificates, which can potentially hinder the rights of the Plaintiff/Applicant for Permission to Announce Divorce. This study aims to determine the procedure for issuing a certificate of absence and its implications for the rights of those seeking justice. This study uses a normative empirical approach, which is a research method based on the empirical experience of the author while practicing as an advocate at the Purwokerto Religious Court Legal Aid Post throughout 2018. The results of the study show that the process of issuing a certificate of absence is hampered by the absence of standard operating procedures, which leads to allegations of maladministration in the form of prolonged delays. In turn, those seeking justice are unable to file for divorce at the Purwokerto Religious Court.